Work Engagement Influences Affective Commitment: Psychological Capital and Perceived Organisation Support As Moderators - Daniel Lie; Kiky Dwi Hapsari Saraswati; David Sugianto Lie (Journal of Indonesian Economy and Business, 2023)
Introduction/Main Objectives: It is well-known that millennials have low levels of attachment towards the organisation.It istherefore necessary to consider ways of retaining them as leavers may affect the organisation financially. Background Problem: Previous studies have consistently shown that work engagement (WE) significantly affects affective commitment (AC). However, the correlation level varies. Hence, a moderator could be affecting the strength of their relationship. Novelty: This research investigated whether psychological capital (PsyCap) and perceived organisation support (POS) could act as moderators. Research Methods: The research was a quantitative and non-experimental study. Researchers usingthe convenience sampling technique and the participants were 111 Indonesian millennial employees who completed questionnaires virtually. Findings/Results: Regression analysis confirmed that WE influenced AC significantly and PsyCap was shown to be a moderator. Further, a three-way interaction revealed that a low level of POS has a significant effect,but only when the level of PsyCap is low, implying that POS is still valid as a moderator (even though only partially). Conclusion: This study concluded that both PsyCap and POS are important for millennial employees. Therefore, it is recommended that management consider these two variables when managing the millennials in their organisation.